The quality of air at archives and the biodeterioration of photographs - Borrego, Sofía (2010)
The objectives of the paper were to evaluate the microbial prevalence inside the buildings of the Photographic Library of the National Archive of the Republic of Cuba (PLNARC) and of the Historical Archive of the Museum of La Plata (HAMP) and to estimate the levels of microbial contamination on photos stored in these repositories. We have also examined some of the physiological features of fungal and bacterial isolates in order to evaluate their potential for biodeterioration. A sedimentation method was used for the microbiological sampling of air, while sterile cotton swabs were used for sampling documents. Petri dishes with appropriate selective culture media were used to isolate fungi and bacteria. The cellulolytic, proteolytic, and amylolytic activities and the production of acids and pigments of the fungal isolates were qualitatively determined. The predominant fungal genera in the air of both institutions were Cladosporium and Penicillium, respectively, for PLNARC and HAMP. At both places, the prevalent bacterial isolates were Gram positive. Among the microbial isolates from photos, various fungal and bacterial isolates were capable of degrading starch and protein and also to excrete acids and pigments, which constitute a high potential risk for the biodeterioration of these documents. Cladosporium and Penicillium, respectively, for PLNARC and HAMP. At both places, the prevalent bacterial isolates were Gram positive. Among the microbial isolates from photos, various fungal and bacterial isolates were capable of degrading starch and protein and also to excrete acids and pigments, which constitute a high potential risk for the biodeterioration of these documents.